The Buddhist Philosophy: : A brief Study - Mishra, Nilachal (Dia-noesis: A Journal of Philosophy, 2024)
The History is well-known to Lord Buddha as Gautama Buddha, Buddha Śākyamuni, Sidhārtha Gautama, and who was born in Lumbini in the Nepalese region of the near Indian border. He was the man of Asian thinkers and was a religious master of all time. His vast contributions to the field of Philosophy, metaphysics, and epistemology highlight Indian history and spiritual paths more and more. In ethics, He explains the threefold understandings of karmas mental, verbal, and physical. In metaphysics Buddha describes the criticism of souls and the real causes of rebirth. He says the ultimate stage of a liberated soul is called ‘Nirvāṇa’.The stage of Nirvāṇa is a very well-known term in Buddhist Philosophy. Buddha explains the many stages of human life and which impressed him extremely. The present paper describes, in brief, the life history of Buddha, his moral teachings to mankind, and the wise expressions of Śrila Prabhupāda on Buddhist Philosophy, etc.